Rapamycin combined with osimertinib alleviated non-small cell lung cancer by regulating the PARP, Akt/mTOR, and MAPK/ERK signaling pathways - Ma, Qingrong; Chen, Kai; Xiao, Haiping (Frontiers in Molecular Biosciences, 2025)
BackgroundsNon-small cell lung cancer (NSCLC), one kind of common malignant tumor, is accompanied by high morbidity and mortality. The effects and related mechanisms of rapamycin (Rapa) combined with osimertinib (Osi) in treating NSCLC are still unclear. Therefore, this study aims to investigate the effects and related mechanisms of Rapa combined with Osi on NSCLC.MethodsIn A549 and PC-9 cells, the Cell Counting Kit-8 (CCK-8) assay was used to select the optimal administrative concentrations of Rapa and Osi and evaluate the cell viability. The Transwell assay and flow cytometry were used to determine the migration, cell cycle, apoptosis, and the level of Reactive Oxygen Species (ROS), respectively. The protein and mRNA expression level of Matrix Metalloproteinase-9 (MMP9), Caspase-3, Microtubule-Associated Protein 1 Light Chain 3 II/I (LC3 II/I), beclin1, Sequestosome 1 (p62), Poly (ADP-ribose) Polymerase (PARP), Mitogen-Activated Protein Kinase (MAPK), Extracellular Signal-Regulated Kinase (ERK), Protein Kinase B (Akt), and Mammalian Target of Rapamycin (mTOR) was determined by Western blot and Quantitative Reverse Transcription Polymerase Chain Reaction (qRT-PCR).ResultsThe optimal administrative concentrations of Rapa and Osi were 0.5 μM and 1 μM, respectively. Rapamycin combined with Osimertinib significantly decreased the viability of cells, the quantity of migrated cells, the levels of ROS, as well as the mRNA and protein expression levels of MMP9 and p62, Caspase-3, LC3 II/I, beclin1. The combination of the two drugs is markedly more effective than the use of drugs alone.ConclusionIn conclusion, the study demonstrated that Rapamycin combined with Osimertinib can inhibit the cell migration, regulate the cell cycle, promote the autophagy and apoptosis, increase the ROS level and regulate the PARP, MAPK/EKR, and Akt/mTOR pathways in A549 and PC-9 cells, providing a novel theoretical basis for their clinical treatment of NSCLC.